2017
DOI: 10.1111/dom.12891
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide effects on beta‐cell, insulin sensitivity and glucose effectiveness in patients with stable coronary artery disease and newly diagnosed type 2 diabetes

Abstract: Liraglutide as add-on to metformin induces a clinically significant improvement in beta-cell function in overweight/obese, high cardiovascular risk patients with newly diagnosed well-controlled T2DM and CAD. The effect of liraglutide on DI is mediated entirely by improved AIRg whereas the effects on Si and Sg are neutral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…We have previously reported that liraglutide reduced hyperglycemia and increased insulin response to glucose, doubling DI with no effect on insulin sensitivity (MINIMOD Millennium analysis) despite an expected loss in net body weight of 2.7 kg (Table ). The Boston Minimal Model of NEFA metabolim also involves additional glucometabolic parameters as compared to placebo.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…We have previously reported that liraglutide reduced hyperglycemia and increased insulin response to glucose, doubling DI with no effect on insulin sensitivity (MINIMOD Millennium analysis) despite an expected loss in net body weight of 2.7 kg (Table ). The Boston Minimal Model of NEFA metabolim also involves additional glucometabolic parameters as compared to placebo.…”
Section: Resultsmentioning
confidence: 93%
“…Excerpts of data published previously in Diabetes, Obesity and Metabolism (2017) and AIR g , DI and SI from MINMOD Millenium analysis …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations